Perception of Students of the Faculty of Ushuluddin and Islamic Studies of the UIN Sumatera Utara towards Jokowi's Political Dynasty - Lili Agustia; Abu Syahrin; Wahyu Wiji Utomo (Getpress Management Journals, 2025)
Political dynasties refer to conditions in which leaders seek to place their family members, relatives, and close relatives in important positions with the aim of establishing a political power within the government structure, both at the national and regional levels. In which, Jokowi's political dynasty has become a quite popular discussion that has developed to date due to the involvement of several members of his family who have direct family ties or relationships with Jokowi. The purpose of this study is to find out how the perception of students of the Faculty of Ushuluddin and Islamic Studies of UIN Sumatera Utara towards Jokowi's political dynasty and what factors caused the emergence of Jokowi's political dynasty according to the student. This research is a qualitative research that is descriptive with an approach that includes political, historical, and phenomenological aspects. The data collection techniques used in this study are interviews and documentation. The results of this study show that there are two perceptions produced by students of the Faculty of Ushuluddin and Islamic Studies towards Jokowi's political dynasty, namely a positive perception that acknowledges the existence of Jokowi's political dynasty and a negative perception that rejects the involvement of the Jokowi family in the political realm as a practice of political dynasties. The factors for the emergence of Jokowi's political dynasty are divided into internal factors and external factors. These internal factors include Jokowi's popularity and ambition. Meanwhile, the external factors are a paternalistic culture, support from political parties, media influence, and lastly, the lack of strict regulations that talk about and limit the practice of political dynasties.